Mapping the Research on Sustainable Finance: Bibliometric Insights from Web of Science and Scopus - Judijanto, Loso (Westscience Press, 2025)
This study presents a bibliometric analysis of sustainable finance research using data exclusively from the WoS and Scopus database and visualization via VOSviewer. The aim is to map the intellectual landscape, identify thematic clusters, and explore global collaboration patterns within this rapidly evolving field. Keyword co-occurrence analysis highlights